The Effect of Policy Uncertainty on Money Demand in CEMAC Countries - Fotie, Andree Kenne; Fotie, Herbert Klauss Kemtsop (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of this paper is to investigate the long run effect of policy uncertainty on money demand for Central African Economic and Monetary Community (CEMAC) countries over the period 1985-2017. We consider a more inclusive measure of policy uncertainty that encompass uncertainty related to economic and political events. Our measure of policy uncertainty is taken from the World Uncertainty Index (WUI) developed by the Policy Uncertainty Group. To estimate the money demand function, we employs panel data estimators that address issues of cross-sectional dependence and parameter heterogeneity. The estimates establish evidence of the long-run relationship between money demand and its determinants. It appears that the demand for domestic money increases with real income meanwhile decreases with the inflation rate. And so, the opportunity cost of holding money is reflected in the rate of inflation. The results associated to the exchange rate show that currency substitution does not hold in the long-run for the sample considered. The most important result is that policy uncertainty has an adverse long-term effect on money demand for CEMAC countries. Our results are robust to alternative panel estimation approaches. Thus, increased uncertainty leads people to hold less cash, while decreased uncertainty leads them to hold more cash.